Analysis of Smart Governance Implementation In Ternate City, North Maluku Province - Aswar, Muh. Hajarul; Nurrahman, Agung; Rahmadanita, Annisa (Jurnal Pallangga Praja (JPP), 2024)
The Ternate City Government has organized the digitization of public services, but based on the Electronic-Based Government System index, the index results obtained are still included in the insufficient category. This study aims to obtain an overview and analyze the implementation of smart governance in Ternate City. The research method used is Quasi Qualitative Method. The results showed that community participation in decision-making in Ternate City was good, with the level of participation and frequency achieved, although there were still people who were not fully involved. The availability of public services and infrastructure still needs to be improved, while government transparency and information accountability have been well achieved. The smart governance strategy in Ternate City already exists, but the policy basis for implementing smart governance is still not fully realized. In conclusion, the implementation of smart governance in Ternate City shows progress in community participation, transparency, and strategy, but still needs improvement in the availability of public services, infrastructure, and supporting policy basis.